Neurophysiological and clinical outcome measures of the impact of electrical stimulation on spasticity in spinal cord injury: Systematic review and meta-analysis - Massey, Sarah; Vanhoestenberghe, Anne; Duffell, Lynsey (Frontiers in Rehabilitation Sciences, 2022)
This systematic review and meta-analysis aims to determine whether non-invasive electrical stimulation (ES) is effective at reducing spasticity in people living with spinal cord injury (SCI). PubMed, Web of Science, Scopus and Cochrane Central Register of Controlled Trials databases were searched in April 2022. Primary outcome measures were the Ashworth scale (AS), Modified Ashworth scale (MAS), Pendulum test and the Penn spasm frequency scale (PSFS). Secondary outcomes were the Hoffman (H)-reflex, motor-evoked potentials (MEPs) and posterior-root reflexes (PRRs). A random-effects model, using two correlation coefficients, (Corr=0.1, Corr=0.2) determined the difference between baseline and post-intervention measures for RCTs. A quantitative synthesis amalgamated data from studies with no control group (non-RCTs). Twenty-nine studies were included: five in the meta-analysis and 17 in the amalgamation of non-RCT studies. Twenty studies measured MAS or AS scores, 14 used the Pendulum test and one used the PSFS. Four measured the H-reflex and no studies used MEPs or PRRs. Types of ES used were: transcutaneous electrical nerve stimulation (TENS), transcutaneous spinal cord stimulation (TSCS), functional electrical stimulation (FES) cycling and FES gait. Meta-analyses of 3 studies using the MAS and 2 using the Pendulum test were carried out. For MAS scores, non-invasive ES was effective at reducing spasticity compared to a control group (p = 0.01, Corr=0.1; p = 0.002, Corr=0.2). For Pendulum test outcomes, there was no statistically significant difference between intervention and control groups. Quantitative synthesis of non-RCT studies revealed that 22 of the 29 studies reported improvement in at least one measure of spasticity following non-invasive ES, 13 of which were statistically significant (p < 0.05). Activation of the muscle was not necessary to reduce spasticity. Non-invasive ES can reduce spasticity in people with SCI, according to MAS scores, for both RCT and non-RCT studies, and Pendulum test values in non-RCT studies. This review could not correlate between clinical and neurophysiological outcomes; we recommend the additional use of neurophysiological outcomes for future studies. The use of TSCS and TENS, which did not induce a muscle contraction, indicate that activation of afferent fibres is at least required for non-invasive ES to reduce spasticity.